LEGAL PROTECTION OF CHILDREN AFTER DIVORCE DIVORCE RELATED TO ACT NUMBER 16 OF 2019 AMENDMENT TO ACT NUMBER 1 OF 1974 CONCERNING MARRIAGE (Decision Study Number 1145/pdt.g/2020/PA.Krw) - Jihan Alfadia; Muhamad Abas; Zarisnov Arafat (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2023)
Child protection is all activities to ensure and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity and values, and receive protection from violence and discrimination. Divorce so far often creates problems inherent in children's rights, namely the right to education, health, maintenance costs and so on. In Law Number 1 of 1974 concerning Marriage, it mentions the rights and obligations between parents and children. It is stated in Law Number 1 of 1974 Article 45 Paragraph 1 namely: